Application rate and nozzles associated with droplet electrification affect the spraying quality in common bean. - MELLO, C. E. L. (2024)
Abstract: The objective of this work was to evaluate the application efficiency of different nozzle tips associated with increasing application rates. A field experiment was conducted in a factorial 3 × 4 randomized block design with four replicates. The first factor consisted of three types of nozzle tips (simple flat fan, hollow cone, and hollow cone with the electrification of the drops), and the second factor constituted the four application rates (50, 100, 200, and 250 L ha-1). Electrostatic technology and a hollow cone tip increased the deposited volume on leaves on the upper and medium strata of the common bean plant, regardless of the application rate used. The increase in the application rate increased the volume of spray solution captured in the upper, medium, and lower strata, the drop density, the volumetric median diameter (VMD), and the percentage of foliar coverage, regardless of the spray tip evaluated. The percentage of leaf coverage on the adaxial and abaxial leaf was not influenced by the simple fan or hollow cone spray tips, with or without the association of electrostatic technology.